SWRO 해수담수화 플랜트 기술 관련 특허 동향 분석 - 조진우; 한지희; 이석헌; 손진식; 양정석; 김동하 (대한상하수도학회, 2008)
Many reports have warned of insufficient water supply in most countries in future and prospected providing safe and clean water become more difficult by lack of access to sustainable drinking water resources. Several facts and figures explained the impact by natural climate change and human activity results in the water scarcity and deterioration. Among many scientific solutions, the seawater desalination using a reverse osmosis membrane, so called SWRO (Seawater Reverse Osmosis) process, has been recognized as one of the most promising alternatives because of its stability and efficiency in producing large amount of drinking water from seawater through desalination by membrane filtration. Recently, in Korea, numerous researches are conducted to develop more productive and cost effective SWRO process for its wide implementation. The objective of this paper is to review the patents concerning SWRO technologies involving the plant engineering, maintenance including pretreatment of seawater and fouling control, module design, and mechanical units development for energy saving. The patents in Korea, U.S., Japan, Europe, and PCT were intensively researched and analyzed to provide the state of the art as well as leading edge technology on SWRO. This information can hopefully suggest meaningful guidelines on future research and development.